Fetal Growth Restriction Induced by Transient Uterine Ischemia–Reperfusion: Differential Responses in Different Mouse Strains. (July 2018) - Thaete, Larry G.; Qu, Xiao-Wu; Neerhof, Mark G.; Hirsch, Emmet; Jilling, Tamas
We characterized fetal and placental growth and uterine and placental inflammation in pregnant C3H/HeOuJ and C57BL/6J mice (strains with different sensitivities to metabolic and circulatory pathologies), using different uterine ischemia/reperfusion (I/R) protocols, to establish and refine a murine model of I/R-induced fetal growth restriction (FGR). Pregnant C3H/HeOuJ mice on gestation day 15 were subjected to unilateral uterine I/R by (1) total blood flow restriction (TFR) by occlusion of the right ovarian and uterine arteries for 30 minutes, (2) partial flow restriction (PFR) by occlusion of only the right ovarian artery for 30 minutes, or (3) sham surgery. Pregnant C57BL/6J mice were treated the same, but on gestation day 14 and with TFR for only 5 minutes due to high sensitivity of C57BL/6J mice to I/R. Four days post-I/R, the animals were euthanized to determine fetal and placental weight and fetal loss and to assay placental myeloperoxidase (MPO) activity. In C3H/HeOuJ mice, TFR/30 minutes induced significantly ( P < .05) lower fetal and placental weights and higher placental MPO activity, compared to controls. The PFR/30 minutes produced the same effects except placental weights were not reduced. In contrast, in C57BL/6J mice, TFR for only 5 minutes was sufficient to induce FGR and increase fetal loss; while PFR/30 minutes lowered fetal but not placental weights and increased fetal loss but not placental MPO activity. In summary, we present the first published model of I/R-induced FGR in mice. We find that mice of different strains have differing sensitivities to uterine I/R, therefore differing I/R response mechanisms.